Ultrafine and Fine Particles and Hospital Admissions in Central Europe. Results from the UFIREG Study - Lanzinger, Stefanie; Schneider, Alexandra; Breitner, Susanne; Stafoggia, Massimo; Erzen, Ivan; Dostal, Miroslav; Pastorkova, Anna; Bastian, Susanne; Cyrys, Josef; Zscheppang, Anja; Kolodnitska, Tetiana; Peters, Annette; et al. (American journal of respiratory and critical care medicine, 2016)
RATIONALE: Evidence of short-term effects of ultrafine particles (UFP) on health is still inconsistent and few multicenter studies have been conducted so far especially in Europe. OBJECTIVES: Within the UFIREG project, we investigated the short-term effects of UFP and fine particulate matter (particulate matter with an aerodynamic diameter less than 2.5 μm [PM2.5]) on daily cause-specific hospital admissions in five Central and Eastern European cities using harmonized protocols for measurements and analyses. METHODS: Daily counts of cause-specific hospital admissions focusing on cardiovascular and respiratory diseases were obtained for Augsburg and Dresden (Germany), 2011-2012; Chernivtsi (Ukraine), 2013 to March 2014; and Ljubljana (Slovenia) and Prague (Czech Republic), 2012-2013. Air pollution and meteorologic data were measured at fixed monitoring sites in all cities. We analyzed city-specific associations using confounder-adjusted Poisson regression models and pooled the city-specific effect estimates using metaanalysis methods. MEASUREMENTS AND MAIN RESULTS: A 2,750 particles/cm3 increase (average interquartile range across all cities) in the 6-day average of UFP indicated a delayed and prolonged increase in the pooled relative risk of respiratory hospital admissions (3.4% [95% confidence interval, -1.7 to 8.8%]). We also found increases in the pooled relative risk of cardiovascular (exposure average of lag 2-5, 1.8% [0.1-3.4%]) and respiratory (6-d average exposure, 7.5% [4.9-10.2%]) admissions per 12.4 μg/m3 increase (average interquartile range) in PM2.5. CONCLUSIONS: Our findings indicated delayed and prolonged effects of UFP exposure on respiratory hospital admissions in Central and Eastern Europe. Cardiovascular and respiratory hospital admissions increased in association with an increase in PM2.5. Further multicenter studies are needed using harmonized UFP measurements to draw definite conclusions on health effects of UFP.
Keywords: Cardiovascular Diseases; Ukrajina; poruchy dýchání; Humans; lidé; Cities; Respiration Disorders; Urban Health; Czech Republic; látky znečišťující vzduch; Air Pollution; Hospitalization; pevné částice; Ukraine; Female; Male; hospitalizace; zdraví ve městech; Particulate Matter; Slovenia; hospital admissions; mužské pohlaví; ultrafine particles; Aged; respiratory; ženské pohlaví; Air Pollutants; kardiovaskulární nemoci; Slovinsko; Germany; velkoměsta; Česká republika; Německo; cardiovascular; znečištění ovzduší; particulate matter; senioři